Financial development and economic growth in Sub-Saharan Africa using system GMM analysis - Temesgen Yaekob Ergano; Sure Pulla Rao (PLoS ONE, 2026)
The study on financial development and economic growth in Sub-Saharan Africa utilises System GMM analysis to investigate the relationship between financial development indicators and regional economic performance. The research findings reveal significant impacts of various financial indicators on economic growth, such as the positive influence of bank liquid reserves on bank assets ratio (R/A), trade openness, and the broad money to total reserves ratio (M/R) on the economic growth of Sub-Saharan Africa. Additionally, the study highlights the negative impact of Credit extended to the private sector by banks within the country (D_bank) on economic development, emphasising the importance of prudent credit allocation to avoid over-indebtedness and financial crises. These results provide valuable insights for policymakers aiming to foster sustainable economic growth in the region by leveraging financial development effectively.